GAME BASED LEARNING MELALUI MEDIA PUZZLE PADA PEMBELAJARAN HADIST KELAS VI SD - Nur Hairun Nisa (ELEMENTARY: Jurnal Inovasi Pendidikan Dasar, 2026)
ABSTRACT Memorization activities remain a dominant feature of Hadith learning in elementary schools; however, such an approach often fails to foster optimal student engagement. At the same time, studies exploring the use of non-digital game-based media in Hadith instruction, particularly those examining students’ learning experiences in depth, are still limited. This situation prompted an exploration of the implementation of Game-Based Learning through puzzle media as an alternative approach to creating a more participatory learning experience. The study was conducted at SDIT Utsman bin Affan, Bekasi City, involving 14 sixth-grade students. Employing a phenomenological approach, data were collected through classroom observations, semi-structured interviews, and documentation throughout the learning process. The analysis was carried out through a series of stages, including data organization, thematic categorization of participants’ experiences, and interpretation of the meanings emerging from their perspectives. The learning process revealed that puzzle-based activities not only helped students recall the sequence of Hadith texts but also fostered motivation, engagement, and self-confidence during learning. Although differences in memorization ability remained a challenge, a more active and enjoyable learning environment was successfully established. The findings suggest that the effectiveness of Game-Based Learning is more closely associated with the design of learning activities that provide meaningful challenges and experiences of achievement than with the use of digital technology itself. This study contributes to the expansion of Game-Based Learning research in Islamic Education by demonstrating the potential of non-digital puzzle media as a contextual, practical, and accessible instructional tool for Hadith learning in elementary schools. ABSTRAK Aktivitas menghafal masih menjadi ciri dominan dalam pembelajaran Hadis di sekolah dasar, tetapi pendekatan tersebut sering belum mampu menghadirkan keterlibatan belajar yang optimal bagi peserta didik. Di sisi lain, kajian mengenai penggunaan media permainan non-digital dalam pembelajaran Hadis, khususnya yang menelaah pengalaman belajar peserta didik secara mendalam, masih relatif terbatas. Situasi tersebut mendorong eksplorasi terhadap penerapan Game Based Learning melalui media puzzle sebagai alternatif untuk menghadirkan pengalaman belajar yang lebih partisipatif. Penelitian ini dilaksanakan di SDIT Utsman bin Affan, Kota Bekasi, dengan melibatkan 14 peserta didik kelas VI. Melalui pendekatan fenomenologi, data dikumpulkan menggunakan observasi, wawancara semi-terstruktur, dan dokumentasi selama proses pembelajaran berlangsung. Analisis dilakukan secara bertahap melalui pengorganisasian data, pengelompokan tema pengalaman, serta penafsiran makna yang muncul dari perspektif partisipan. Dinamika pembelajaran memperlihatkan bahwa penyusunan puzzle tidak hanya membantu peserta didik mengingat urutan lafaz hadis, tetapi juga membangun motivasi, keterlibatan, dan rasa percaya diri selama belajar. Meskipun perbedaan kemampuan hafalan masih menjadi tantangan, suasana belajar yang lebih aktif dan menyenangkan tetap dapat terbentuk. Temuan ini memperlihatkan bahwa efektivitas Game Based Learning lebih berkaitan dengan kemampuan desain aktivitas belajar dalam menghadirkan tantangan dan pengalaman keberhasilan daripada dengan penggunaan teknologi digital. Kontribusi penelitian terletak pada perluasan kajian Game Based Learning dalam Pendidikan Agama Islam melalui pemanfaatan media puzzle non-digital yang kontekstual, sederhana, dan mudah diterapkan pada pembelajaran Hadis di sekolah dasar.